Development of Augmented Reality based Power Spin Learning Media Assemblr 3D PJBL model for Reaction and Timing Pattern Problems - Rohmad Apriyanto; Hilmy Aliriad; Mohamad Da’i; Adi S; Suningsih, Suningsih; Wiji, Aris (UNIB Press, 2024)
This research was conducted to find out how the role of augmented reality technology in solving problems in the field regarding reaction patterns and timing in table tennis power spin shot techniques with the PjBL approach. the final product of this research is in the form of 3D augmented reality assemblr technology that can be applied via smartphone by scanning the barcode. The method used is R&D with the development design used is ADDIE. the stages in the model, namely analysis, design, development, implementation and evaluation. Augmented reality assemblr 3D product in the form of a barcode, which there are 6 main menus on the front display. the results of research on the subject of PJKR students in semester III of class 2023 show that augmented reality learning media can be implemented well with the results of testing Assemblr 3D AR (Augmented Reality) learning media obtained an average score of 90.77% with the category (very good). With an indicator of suitability of 89%, understandability of 93.5%, usefulness of 90%, skill development and learning motivation of 91.75 media functionality and convenience of 90%. Based on the results of the augmented reality test, it can be concluded that AR (Augmented Reality) technology is feasible to use as a learning media feasible to use as a medium for learning table tennis UNUGIRI PJKR students.